Financial Incentives and Health Coaching to Improve Physical Activity Following Total Knee Replacement: A Randomized Controlled Trial. Issue 5 (12th April 2018) - Losina, Elena; Collins, Jamie E.; Deshpande, Bhushan R.; Smith, Savannah R.; Michl, Griffin L.; Usiskin, Ilana M.; Klara, Kristina M.; Winter, Amelia R.; Yang, Heidi Y.; Selzer, Faith; Katz, Jeffrey N.
Abstract : Objective: Most persons who undergo total knee replacement (TKR) do not increase their physical activity following surgery. We assessed whether financial incentives and health coaching would improve physical activity in persons undergoing TKR. Methods: We designed a factorial randomized controlled trial among persons undergoing TKR for osteoarthritis. Subjects underwent normal perioperative procedures, including postoperative physical therapy, and were assigned to 1 of 4 arms: attention control, telephonic health coaching (THC), financial incentives (FI), or THC + FI. We objectively measured step counts and minutes of physical activity using a commercial accelerometer (Fitbit Zip) and compared the changes from pre‐TKR to 6 months post‐TKR across the 4 study arms. Results: Of the 202 randomized subjects, 150 (74%) provided both pre‐TKR and 6 months post‐TKR accelerometer data. Among completers, the mean ± SE daily step count at 6 months ranged from 5, 619 ± 381 in the THC arm to 7, 152 ± 407 in the THC + FI arm (adjusting for baseline values). Daily step count 6 months post‐TKR increased by 680 (95% confidence interval [95% CI] −94, 1, 454) in the control arm, 274 (95% CI −473, 1, 021) in the THC arm, 826 (95% CI 89, 1, 563) in the FI arm, and 1, 808 (95% CI 1, 010, 2, 606) in the THC + FI arm. Weekly physical activity increased by mean ± SE 14 ± 10, 14 ± 10, 16 ± 10, and 39 ± 11 minutes in the control, THC, FI, and THC + FI arms, respectively. Conclusion: A dual THC + FI intervention led to substantial improvements in step count and physical activity following TKR. Abstract : Video Abstract Video Abstract